2019
DOI: 10.47312/aefr.v3i02.207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Non Performing Financing, Financing to Deposit Ratio and Operating Expense to Operating Income Ratio (Bopo) to Profitability

Abstract: <p><em>The issues raised in this study are: to determine, explain and analyze profitability, Non Perfroming Loan, Financing to Deposit Ratio and Operating Expense to Operating Income in Bank of sharia and the partial effect and simultaneous of NPF, FDR and Operating Expense to Operating Income ratio  to Profitability Bank of sharia Period 2014 -2016.</em></p><p><em>The number of samples taken 12 Bank of sharia in the study period with saturated sampling technique. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…So that there was no influence between the Financing to Deposit Ration (FDR)(X3) variable on Return On Asset Y, or in other words, H 0 was accepted and H a was rejected. This result in line with Ikhsan, et., al, (2018), Suartini, et., al, (2019), Husna & Satria (2019), Asiyah, et. al., (2021), Ichsan, et.…”
Section: Multiple Regressionmentioning
confidence: 95%
See 1 more Smart Citation
“…So that there was no influence between the Financing to Deposit Ration (FDR)(X3) variable on Return On Asset Y, or in other words, H 0 was accepted and H a was rejected. This result in line with Ikhsan, et., al, (2018), Suartini, et., al, (2019), Husna & Satria (2019), Asiyah, et. al., (2021), Ichsan, et.…”
Section: Multiple Regressionmentioning
confidence: 95%
“…However, the ROA and NPF variables do not affect the profit-sharing of mudharabah deposits. Suartini, et. al., (2019) testing profitability, Non Perfroming Loan, Financing to Deposit Ratio and Operating Expense to Operating Income in Bank of sharia and the partial effect and simultaneous of NPF, FDR and Operating Expense to Operating Income ratio to Profitability Bank of sharia Period 2014 -2016 found that NPF, FDR and ROA simultaneously positive and significant impact on profitability Bank of sharia in the study period.…”
Section: Introductionmentioning
confidence: 99%
“…Rasio ini menggambarkan jumlah aset yang dibutuhkan untuk menghasilkan laba bersih. Menurut (Suartini et al, 2018), ROA digunakan oleh manajemen perusahaan untuk mengevaluasi efektivitas dan efisiensi pengelolaan seluruh aset perusahaan. Jika nilai ROA tinggi, maka perusahaan dikatakan efisien jika mempertahankan jumlah aset yang sama namun menghasilkan laba yang lebih besar, begitu pula sebaliknya.…”
Section: Pengaruh Return On Asset Terhadap Harga Sahamunclassified
“…Operating Costs Operating Income (BOPO) is a ratio used to measure the level of ability of bank management to efficiently control operational costs to operating income (Suartini et al, 2018). The research findings by Nengsih (2020) show that BOPO affect PDM.…”
Section: Literature Reviewmentioning
confidence: 99%